2017
DOI: 10.1007/s12253-017-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1-PredictedmicroRNAs Dysregulation Contributes to Tumor Progression in Ewing Sarcoma

Abstract: Over the last decade, the rho-associated kinases and several metastasis-associated microRNAs have emerged as important contributors of tumor invasion. However, despite prominence, our understanding of their involvement in the metastatic potential of Ewing Sarcoma (EWS) is incomplete. The expression profiles of ROCK1 or ROCK2 and miR-124-3p, miR-138-5p, miR-139-5p, miR-335-5p and miR-584-5p (all of which were previously predicted or validated to regulate these kinases) were evaluated through qRT-PCR and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Therefore, we inferred that miR-124-3p may be an exception in the miR-124 family, and then we collected articles on miR-124 to explore the detailed results. As we found, miR-124-3p directly targeted PDCD6 to inhibit metastasis in breast cancer [15] and cooperated with ROCK1 to reduced procession in Ewing Sarcoma [16]. Luo et al reported that miR-124-3p suppresses glioma aggressiveness by targeting Fra-2 [17].…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, we inferred that miR-124-3p may be an exception in the miR-124 family, and then we collected articles on miR-124 to explore the detailed results. As we found, miR-124-3p directly targeted PDCD6 to inhibit metastasis in breast cancer [15] and cooperated with ROCK1 to reduced procession in Ewing Sarcoma [16]. Luo et al reported that miR-124-3p suppresses glioma aggressiveness by targeting Fra-2 [17].…”
Section: Discussionmentioning
confidence: 78%
“…In several human cancers, hsa-miR-335 has multiple roles in carcinogenesis [21][22][23][24]. Although little is known of the role of miR-335-3p in lung cancer, in several other cancers, miR-335-3p is down-regulated [25][26][27][28]. The expression of miR-335-3p in adenocarcinoma of the lung and the mechanism remain unknown, and there have been no previous studies on the miR-335-3p/COPB2 axis in adenocarcinoma of the lung or other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, miR-335 disturbed proliferation and migration, while promoting radiosensitivity of melanoma by inhibiting ROCK1. The miR-335/ROCK1 axis regulated multiple functions, including tumor progression (19)(20)(21), myocardial ischemia/reperfusion (22), and chondrogenesis (23). Lynch and colleagues firstly illustrated the negative feedback loop among miR-335/ROCK1-noncanonical TGF-β signaling and MYCN (24).…”
Section: Discussionmentioning
confidence: 99%